1997
DOI: 10.1002/(sici)1096-9071(199709)53:1<19::aid-jmv4>3.0.co;2-t
|View full text |Cite
|
Sign up to set email alerts
|

Nucleotide and amino acid sequence variations in the L1 open reading frame of human papillomavirus type 6

Abstract: Human papillomavirus (HPV) type 6 induces benign tumors such as condyloma acuminata and laryngeal papilloma. The HPV-6 DNA has been thought to be a heterogeneous group of subtypes and variant-types. To examine sequence variations of the HPV-6 L1 ORF, we analyzed by single-strand conformation polymorphism (SSCP) and by DNA sequencing 21 specimens from condyloma acuminata and laryngeal papilloma that harbor HPV-6 DNA. PCR products of HPV-6 DNA were digested with 6 restriction enzymes yielding 8 fragments, which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1999
1999
2009
2009

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Specific silent nucleotide substitutions at eight fixed locations in the HPV-6 L1 ORF were observed in 76 % of isolates. These eight substitutions have been previously described in either HPV-6a (Hofmann et al, 1995) or HPV-6 isolates from India, Japan, Philippines and the United States (Icenogle et al, 1991 ;Suzuki et al, 1997). These results indicate that the prototype HPV-6b is not the predominant subtype W. Caparro!…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Specific silent nucleotide substitutions at eight fixed locations in the HPV-6 L1 ORF were observed in 76 % of isolates. These eight substitutions have been previously described in either HPV-6a (Hofmann et al, 1995) or HPV-6 isolates from India, Japan, Philippines and the United States (Icenogle et al, 1991 ;Suzuki et al, 1997). These results indicate that the prototype HPV-6b is not the predominant subtype W. Caparro!…”
Section: Discussionmentioning
confidence: 99%
“…Icenogle et al (1991) described several nucleotide changes within a 253 nt fragment of the L1 ORF from different geographical isolates of HPV-6, but reported no amino acid substitutions. Suzuki et al (1997) reported, in addition to several silent nucleotide substitutions, an Asn-to-Thr substitution in aa 55 of the L1 protein. However, it is not known whether this substitution affects the stability, yield and\or morphology of the resulting VLPs compared to those derived from the prototype HPV-6b L1 sequence.…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations